Education on the use of compost blocks for chili cultivation for coastal sand farming groups - Susanawati Susanawati; Mulyono Mulyono; Heri Akhmadi (Universitas Muhammadiyah Magelang, 2023)
High temperatures in the land are one of the obstacles faced in cultivating chilies on coastal sand, resulting in nutrients being easily lost and not lasting long. An alternative solution to overcome this problem is to use compost block planting media. This service activity aims to provide knowledge and skills in utilizing agricultural waste for compost as a medium for planting chilies in beach sand. The service methods used are (1) Counseling and Focus Group Discussions about compost blocks; (2) training and demonstration on making block compost; (3) demonstration plot for the use of compost blocks for chili plants, and (4) monitoring and evaluation before, during, and after the activity takes place. The results of service activities show that partners are very enthusiastic about participating in all activities, as shown by an increase in partners' knowledge about compost blocks by 47%. There are 12% of chili plants that die when planted using compost blocks. Meanwhile, chili plants planted conventionally without compost blocks produced more dead plants, namely 30%.